2021
DOI: 10.15181/rfds.v29i3.2006
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Emotional Intelligence in Vocational Education as a Method to Achieve Employability of Graduates

Abstract: Emotional intelligence can play an important role in an individual's education and career success. The purpose of this study is to evaluate the opinion of employers on the importance of competencies related to emotional intelligence in the recruitment process in Latvia, as well as the extent to which these competencies can be developed in vocational education and training. Total of 750 companies participated in this research, rating the importance of competencies and the performance of vocational education ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other studies are indicating that a stronger focus on extra-curriculum activities and a diversification of teaching and learning methods to promote more social, self-management and emotional competences (Līce, 2019a) and intentions to encourage each student to take responsibility about his personal growth and his ambitions (Kiris, 2019) are the right development path for the Latvian VET system. This is supported by other findings, indicating positive relationship between employability and the opportunity to develop planning and selforganising competencies in vocational education (Līce, 2019b). The majority of Latvian employers support the introduction of WBL in the Latvian VET system but does not feel fully prepared to do actually offer the training positions (Buligina et al, 2014).…”
Section: Latviamentioning
confidence: 54%
“…Other studies are indicating that a stronger focus on extra-curriculum activities and a diversification of teaching and learning methods to promote more social, self-management and emotional competences (Līce, 2019a) and intentions to encourage each student to take responsibility about his personal growth and his ambitions (Kiris, 2019) are the right development path for the Latvian VET system. This is supported by other findings, indicating positive relationship between employability and the opportunity to develop planning and selforganising competencies in vocational education (Līce, 2019b). The majority of Latvian employers support the introduction of WBL in the Latvian VET system but does not feel fully prepared to do actually offer the training positions (Buligina et al, 2014).…”
Section: Latviamentioning
confidence: 54%
“…This literature review also illustrated how interventions to improve emotional competences could be adapted to the VET context (particularly the cohabitation of two training places, the heterogeneity of the considered professions, their priorities in terms of emotional management, etc.). In addition, a recent study investigated EI in VET and showed its relevance in improving employability (Līce & Sloka, 2019). However, the role of EI in VET continues to be underestimated and can benefit from further investigation, especially in training sectors where emotions play a central role, such as health and social care.…”
Section: Ei In the Vet Contextmentioning
confidence: 99%